Changes in the concept of university in 20th century Peru: From the humanistic university to the entrepreneurial university - Maguiña, Juan Arturo; Dore, Rosemary (Education Policy Analysis Archives, 2022)
This article presents bibliographic research on the historical transformations of the idea of the university in Peru, mainly in the 20th century. The idea of the university, in principle, is linked to historical social and economic transformations, to conjunctural political pressures, but also to hegemonic ideological and philosophical conceptions about education. For contextualization purposes, a scheme of historical periodization of the idea of the Peruvian university is proposed: first, as an evangelizing institution; second, as a scholastic institution that teaches professionals; third, in the 20th century, as a training institution for researchers and socially and politically committed intellectuals, and contemporaneously, fourth, as an institution that produces professionals for the market (late 20th century and early 21st century). We identified a diversity of ideas about the role of the university in Peruvian society throughout the 20th century that ranged from the humanist, enlightened, and liberal ideal —currently in retreat— to productive and mercantile pragmatism, currently hegemonic. We conclude that the idea of a university in Peru is subject to the ups and downs of Peruvian socio-economic development.